CALL and SLA Theory: Developing A Framework to Analyze Web-based Materials for Teaching Listening Skills - Khoiriyah Khoiriyah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
Listening skills, considered by many to be the most critical language learning skills, have yet to emerge a variety of problems for learners. In order to have an effective listening class, teachers can use one of the many technology-enhanced language learning tools, web-based materials. In this article attempts have been made to make a comprehensive review on the grounded theory of Computer-Assisted Language Learning (CALL) and Second Language Learning (SLA) related to the use of web-based resources in teaching and learning English, especially for listening skills. This article also proposes a framework for conducting CALL evaluation that is worthy for website materials. The result yields a good guideline for teachers to make judgment or decision in choosing the most congruent web-based sources for teaching listening skills. As a result, teachers are able to adapt a proper teaching materials and methodology for listening skills.